The Evolution of Gastrointestinal Bleeding: A Holistic Investigation of Global Outputs with Bibliometric Analysis - Kudu, Emre; Danış, Faruk (Turkish Journal of Gastroenterology, 2022)
Background: Gastrointestinal bleeding is one of the main presentations in emergency department admissions. Although there has been much improvement in prevention, diagnosis, and treatment recently, patients with GIB still have high morbidity and mortality. This study aimed to analyze the scientific articles on gastrointestinal bleeding published between 1980 and 2020 using statistical and bibliometric methods. Methods: Articles about gastrointestinal bleeding published between 1980 and 2020 were downloaded using the Web of Science database and analyzed using statistical methods. Network visualization maps were used to identify trending topics. Correlation studies were evaluated using Spearman’s correlation coefficient. Nonlinear regression analysis (exponential model) was used to estimate the number of articles in future years. Results: A total of 12 568 publications about gastrointestinal bleeding were found. Forty percent (n = 5033) of these publications were articles. The top 3 contributing countries to the literature were the United States of America (1646, 32.7%), the United Kingdom (433, 9%), and Germany (391, 7.7%). The top three journals with the most publications were Gastrointestinal Endoscopy (172), American Journal of Gastroenterology (165), and Digestive Diseases and Sciences (161). The effect of countries’ gross domestic product levels on article productivity on gastrointestinal bleeding was significant (r = 0. 770, P < .001). Conclusion: In this comprehensive study, a summary of 5033 articles was presented. We think that these detailed analyses will be a quick source to show the past, present, and future of this subject to those who are currently working on gastrointestinal bleeding. Cite this article as: Kudu E, Danış F. The evolution of gastrointestinal bleeding: A holistic investigation of global outputs with bibliometric analysis. Turk J Gastroenterol. 2022;33(12):1012-1024.